MIDWIFERY CARE FOR MATERNITY WITH AN INTERVENTION FOCUS CLASSICAL MUSIC GIVING TO LOWER PAIN INTENSITY IN THE TIME OF LABOR AT PURWODADI 1 HEALTH CENTER - Putri Damayanti; Dhiyan Nany Wigati (The Shine Cahaya Dunia Kebidanan, 2023)
Background; Labor is a series of events that begins when the baby is born and ends when the placenta and membranes are pushed out of the mother's body. Most of the maternity mothers experience pain in the first stage of labor. The purpose of the study was to provide midwifery care with a focus on intervention of classical music therapy to reduce pain intensity in the first stage of labor. Method; The research design that the researcher uses is a case study research design. This type of descriptive case study research uses participatory observation method. The subjects in this study were mothers who gave birth in the first stage. Result; The results showed the diagnosis of Ny. A with pain disorder. Evaluation of classical music therapy in the case of Ny. A with pain there is a reduction from a scale of 4 to a scale of 3. Conclusion; The problem of labor pain in the first stage of Ny. A is resolved.